2019
DOI: 10.1126/sciadv.aaw6671
|View full text |Cite
|
Sign up to set email alerts
|

Genes lost during the transition from land to water in cetaceans highlight genomic changes associated with aquatic adaptations

Abstract: The transition from land to water in whales and dolphins (cetaceans) was accompanied by remarkable adaptations. To reveal genomic changes that occurred during this transition, we screened for protein-coding genes that were inactivated in the ancestral cetacean lineage. We found 85 gene losses. Some of these were likely beneficial for cetaceans, for example, by reducing the risk of thrombus formation during diving (F12 and KLKB1), erroneous DNA damage repair (POLM), and oxidative stress–induced lung inflammatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(133 citation statements)
references
References 84 publications
5
128
0
Order By: Relevance
“…This screen revealed that the single coding exon of TLR5 exhibits stop codon mutations, smaller frameshifting insertions or deletions, or larger deletions in the genome assemblies of 17 species belonging to 14 distinct lineages (gorilla, orangutan, guinea pig, rabbit, pig, alpaca, Yangtze river dolphin, bighorn sheep, Weddell seal, Hawaiian monk seal, walrus, Malayan and Chinese pangolins, little brown bat, elephant, armadillo). Since we have previously shown that apparent gene-inactivating mutations can sometimes be sequencing or assembly errors (Hecker, et al 2017;Sharma, et al 2018b;Hecker, et al 2019a;Huelsmann, et al 2019), we carefully validated the correctness of all such putative mutations and performed additional analyses to establish which of these 17 species truly lost TLR5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This screen revealed that the single coding exon of TLR5 exhibits stop codon mutations, smaller frameshifting insertions or deletions, or larger deletions in the genome assemblies of 17 species belonging to 14 distinct lineages (gorilla, orangutan, guinea pig, rabbit, pig, alpaca, Yangtze river dolphin, bighorn sheep, Weddell seal, Hawaiian monk seal, walrus, Malayan and Chinese pangolins, little brown bat, elephant, armadillo). Since we have previously shown that apparent gene-inactivating mutations can sometimes be sequencing or assembly errors (Hecker, et al 2017;Sharma, et al 2018b;Hecker, et al 2019a;Huelsmann, et al 2019), we carefully validated the correctness of all such putative mutations and performed additional analyses to establish which of these 17 species truly lost TLR5.…”
Section: Resultsmentioning
confidence: 99%
“…In general, loss of a gene can be due to relaxed selection to preserve its function or provide an evolutionary advantage (Albalat, et al 2016;Sharma, et al 2018a;Hecker, et al 2019b;Huelsmann, et al 2019). Interestingly, in humans, the TLR5 stop codon mutation is associated with both positive and negative consequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the contribution of mutations in such genes or regulatory elements to the evolution of a trait requires an experimentallytractable system, such as the mouse, where specific mutations can be introduced and their effects quantified. Gene knockout studies in mice contributed to our understanding of the functional role of many genes naturally lost in a variety of mammalian species (39)(40)(41)(42)(43)(44)(45)(46). However, the effect of other, much more frequent genomic changes, such as amino-acid changing mutations in protein-coding sequences and sequence changes in regulatory elements has rarely been explored.…”
Section: Discussionmentioning
confidence: 99%
“…However, their overly inclusive approach predicted hundreds of gene losses per species across 62 mammals, of which only 21 total were reported, presumably because manual inspection found many loss predictions to 3 be spurious. Similar technique was used to further semi-manually annotate 85 gene losses in cetaceans [16]. Other computational approaches for gene annotation, like the Ensembl pipeline [17], combine ab initio predictions with protein sequence evidence [18] and with gene models inferred from RNA-seq data.…”
Section: Introductionmentioning
confidence: 99%